(untitled) - Park, Chan S. (Upper Saddle River, N.J., 2007)
A second revised edition aimed at introductory engineering economics courses. It provides a modern approach to all aspects of financial analysis, investment, risk analysis and capital budgeting. Spreadsheets are used to model and analyse economic decisions in product design. Includes examples and case studies.
Keywords: Kinh tế kỹ thuật,Engineering economy